The impact of the intensity of media use on potential tourists’ risk perception and travel protective behavioral intentions in COVID-19 - Sun, Ruihong; Ye, Xinliang; Tang, Jianping; Yang, Jiexi; Scott, Noel (Frontiers in Psychology, 2023)
Due to COVID-19, potential travelers are seeking more information about their trips to manage perceived risk. This suggests a need to examine potential tourists' perceptions of epidemic risks and their protective behaviors when exposed to different media sources. This research examines the relationship between the use intensity of new or traditional media, epidemic risk perception and tourism protection behavior intention. Some 491 valid questionnaires were collected from Shanghai, China. Factor, path, and effect analysis using SPSS and AMOS showed differences in the effect of media type. New media had a significant positive correlation with epidemic risk perception and tourism protection behavior while use intensity of traditional media had a significant negative correlation with the perception of epidemic risk, and no significant impact on the intention of tourism protection behavior. Further, epidemic risk perception mediated the relationship between media use intensity and tourism protection behavior. The paper discusses these results and their impact on tourism enterprise marketing strategies and government policy in the post Covid-19 era.